The Impact of Illegal Divorce on Women's Rights According to the Compilation of Islamic Law - Adrianto, Adrianto; Sulastri, Widia; Mardianton, Mardianton; Suarni, Lili; Afifa Zahra, Lilis (Samara: Journal of Islamic Law and Family Studies, 2024)
Divorce can be legally obtained through religious courts. However, many married couples still choose to divorce outside of court, a practice known as “illegal divorce.” As a result, the husband fails to fulfill his obligation to provide iddah and mut’ah maintenance to his wife. This study aims to investigate the impact of women's rights on iddah and mut’ah maintenance following illegal divorce in the village of Koto Panai. The research method employed is qualitative, utilizing a legal-empirical approach in the form of field research. The research informants include 5 families (husband and wife) post-illegal divorce, community leaders, and the Religious Affairs Office. Data collection methods include observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using triangulation techniques. The research results indicate that the impact of women's rights on iddah maintenance after illegal divorce is significant, both economically, psychologically, and socially. Illegal divorce can also have various negative impacts on women, men, and children. Illegal divorce can also have various negative impacts, not only on women and men, but also on children in families after illegal divorce. The causes are diverse, such as economic and communication factors. Meanwhile, the social impact of illegal divorce has negative consequences for women, such as loss of economic rights, child custody rights, and social stigma. Based on the results of this study, we identified the social impact of illegal divorce on women's rights, as well as an analysis of the factors that influence the social impact of illegal divorce on women's rights.